Analisis pengaruh variasi jumlah pelapisan dan jarak pelapisan spray coating pada baja AISI 1020 terhadap kekasaran dan laju korosi dengan media air garam - Iqbal Rizky Setyawan; Afira Ainur Rosidah (Badan Kerja Sama Teknik Mesin Indonesia, 2023)
AISI 1020 steel is a low carbon steel commonly used for ship hulls. The disadvantage of steel is that it corrodes easily. One way to slow down the rate of corrosion is by coating. Coating or plating is the method most often used to slow down the corrosion rate because it is more effective, easy to apply. This research aims to determine the effect of the number of coatings and the spacing of spray coatings on surface roughness and corrosion rate. Variations used are variations in the amount of coating 1 layer, 2 layers, dan 3 layers, also variations in coating distance of 10 cm, 15 cm, and 20 cm. The method used to calculate the corrosion rate is weight loss. The results showed that the best roughness on the 3-layer with 10 cm specimen was 0.857 μm and the lowest corrosion rate was on the 3-layer with 20 cm specimen with a value of 2.376 mpy. The best distance for coating is not too close and not too far. If the distance is too close, the paint will melt (runs) and the amount of paint that sticks will be too large, so the layer will be too thick and smooth. The coating distance that is too far causes the paint to stick a little and causes the paint to dry before it sticks to the media, so that it becomes thin and rough. The more the number of coatings, the better it inhibits the corrosion rate.